On the origins of the multinational premium - José Fillat; Stefania Garetto (Federal Reserve Bank of Boston, 2021)
How do foreign direct investment (FDI) dynamics relate to the risk premium of a firm? To answer this question, we compare the stock returns of US firms with different FDI and mergers and acquisitions (M&A) exposure to study the evolution of stock returns as firms expand into foreign markets. We document three empirical regularities. First, there are cross-sectional risk premia associated with both multinational activity and mergers and acquisitions. Second, firm-level stock returns decline when a firm undertakes M&A activity and with merger deepening. Third, future multinational acquirers already have higher stock returns compared with domestic non-acquirers prior to entering foreign markets, indicating that cross-sectional returns differentials are driven by selection based on common unobserved firm characteristics. We find that CEOs play a role in explaining the relationship between firms' risk premia and foreign expansion. To rationalize these facts, we develop a dynamic model in which management attitudes shape the relationship between firm characteristics, selection into FDI, and risk premia.
Keywords: F12; F23; F36; 330; multinational firms; mergers and acquisitions; management; stock returns